Optimising expert dyad performance in acute care settings: a scoping review protocol. Issue 7 (13th July 2021) - Walker, Katie; Asoodar, Maryam; Rudolph, Jenny; Meguerdichian, Michael; Yusaf, Tricia; Campbell-Taylor, Kimberly; van Merriënboer, Jeroen
Abstract : Introduction: When there is miscommunication and poor coordination between experienced clinician dyads, teamwork suffers. Research on expert learning practices for the smallest team, and arguably the most important team, the healthcare dyad, is limited. The objective of this study is to map the extent and range of evidence available on learning practices which experienced dyads use, to achieve excellent performance, and to identify the gaps in effective practice. This will guide future research, policy and practice. Methods and analysis: We are using the JBI methodology for scoping reviews and the Preferred Reporting Items for Systematic Reviews and Meta-analyses extension for Scoping Reviews Extension Fillable Checklist, searching for literature that meets the inclusion criteria. The searches will be conducted using Maastricht University's Libsearch, which includes MEDLINE, Education Resources Information Center and PsycINFO and a second search on Web of Science online databases. We will search grey literature and references of selected sources. Search limits include sources from 2016 to 2021, using English language only. A data extraction tool was developed, and charting will use a thematic analysis approach. Implications and dissemination: This review will be the first to examine the learning practices that experienced dyads use, which ensures excellent performance in acute care settings. The findings will be used to develop best-practices and shared with New York City hospital system. Dissemination will occur through peer-reviewed publications and at healthcare conferences.